2009
DOI: 10.1134/s1054660x09040434
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of biomedical signals by flicker-noise spectroscopy: Identification of photosensitive epilepsy using magnetoencephalograms

Abstract: The flicker-noise spectroscopy (FNS) approach is used to determine the dynamic characteristics of neuromagnetic responses by analyzing the magnetoencephalographic (MEG) signals recorded as the response of a group of control human subjects and a patient with photosensitive epilepsy (PSE) to equiluminant flickering stimuli of different color combinations. Parameters characterizing the analyzed stochastic biomedical signals for different frequency bands are identified. It is shown that the classification of the p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…An example that is often quoted as evidence of this fact is the application of FNS in the analysis of the effect of different types of medical treatment on the dynamics of index finger tremor in Parkinsonian patients [65]. Moreover, Timashev et al [52] used FNS for the identification of the photosensitive epilepsy. Their results suggest that FNS is a promising method of early diagnosis, not only for the photosensitive epilepsy but also for other neurodegenerative diseases such as Parkinson’s, Alzheimer’s, Huntington’s, amyotrophic lateral sclerosis and schizophrenia.…”
Section: Introductionmentioning
confidence: 99%
“…An example that is often quoted as evidence of this fact is the application of FNS in the analysis of the effect of different types of medical treatment on the dynamics of index finger tremor in Parkinsonian patients [65]. Moreover, Timashev et al [52] used FNS for the identification of the photosensitive epilepsy. Their results suggest that FNS is a promising method of early diagnosis, not only for the photosensitive epilepsy but also for other neurodegenerative diseases such as Parkinson’s, Alzheimer’s, Huntington’s, amyotrophic lateral sclerosis and schizophrenia.…”
Section: Introductionmentioning
confidence: 99%
“…In the latter cases, this concerns not only an analysis of known atmospheric aerosol components, but also an analysis of biological and medical responses of flora and fauna of the biosphere to the impacts of aerosols. Such studies are feasible, because the FNS method has demonstrated its capabilities in analyzing of responses of native systems [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…It is widely known that the disease received after cases of mass attacks in Japan during the demonstration of the animated series "Pokemon." Previously, the individual characteristics of the subjects' reactions have been identified based on the method of flickernoise spectroscopy on a red-blue and red-green incentive, and set the degree of contribution of various types of irregularities in normal and pathological dynamics of brain activity signals [29]. The Fractal Analysis of the Images and Signals in Medical Diagnostics http://dx.doi.org/10.5772/intechopen.68167…”
Section: Self-similar Mechanism Neuromagnetic Dynamics Of Brain Activitymentioning
confidence: 99%